Pengalaman Trauma Anak Akibat Perceraian Orang Tua dan Dampaknya Terhadap Fokus Belajar: Penelitian - Rinna Yuanita Kasenda; Chrispin Injillia Direno; Eva Desanta Claudya Thomas; Mariam Kerenhapukh Kere; Ramita Pongrangga; Ericka Runtunuwu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Parental divorce is a family event that can cause psychological distress in children. This study aims to describe children’s traumatic experiences following parental divorce and their implications for children’s ability to maintain learning focus. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, direct observations, and document analysis. The informants consisted of children who experienced parental divorce, parents or guardians, and counselors involved in child assistance. The findings indicate that children experience various emotional reactions such as prolonged sadness, anxiety, feelings of loss, and changes in attitudes and behavior. These conditions affect learning focus, which is reflected in decreased concentration, weakened learning motivation, and declining academic achievement. In addition, support from the family, the role of teachers at school, and counseling assistance have been shown to help children in the process of emotional recovery and improvement of learning focus. This study emphasizes that trauma resulting from parental divorce requires serious attention because it directly affects children’s readiness to learn.